2014
DOI: 10.1074/jbc.m114.565457
|View full text |Cite
|
Sign up to set email alerts
|

The Retinal Pigment Epithelium Utilizes Fatty Acids for Ketogenesis

Abstract: Background: RPE cells derive fatty acids from phagocytized photoreceptor outer segments. Results: RPE cells metabolize palmitate to produce ␤-hydroxybutyrate (␤-HB), a ketone body the retina can use as a metabolic substrate. Conclusion: RPE cells produce ␤-HB as a potential substrate for photoreceptor cells in the outer retina. Significance: This is a novel form of RPE-retina interaction that may be important for retinal cell health and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 39 publications
6
138
0
Order By: Relevance
“…It remains possible that in ketotic states, liver-derived ketone bodies could be renoprotective, but evidence for renal ketogenesis requires further substantiation. Compelling evidence that supports true extrahepatic ketogenesis was presented in RPE (Adijanto et al, 2014). This intriguing metabolic transformation was suggested to potentially allow RPE-derived ketones to flow to photoreceptor or Müller glia cells, which could aid in the regeneration of photoreceptor outer segment.…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 97%
See 1 more Smart Citation
“…It remains possible that in ketotic states, liver-derived ketone bodies could be renoprotective, but evidence for renal ketogenesis requires further substantiation. Compelling evidence that supports true extrahepatic ketogenesis was presented in RPE (Adijanto et al, 2014). This intriguing metabolic transformation was suggested to potentially allow RPE-derived ketones to flow to photoreceptor or Müller glia cells, which could aid in the regeneration of photoreceptor outer segment.…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 97%
“…Anaerobic bacterial fermentation of complex polysaccharides yields butyrate, which is absorbed by colonocytes in mammalians for terminal oxidation or ketogenesis (Cherbuy et al, 1995), which may play a role in colonocyte differentiation (Wang et al, 2016). Excluding gut epithelial cells and hepatocytes, HMGCS2 is nearly absent in almost all other mammalian cells, but the prospect of extrahepatic ketogenesis has been raised in tumor cells, astrocytes of the central nervous system, the kidney, pancreatic β cells, retinal pigment epithelium (RPE), and even in skeletal muscle (Adijanto et al, 2014; Avogaro et al, 1992; El Azzouny et al, 2016; Grabacka et al, 2016; Kang et al, 2015; Le Foll et al, 2014; Nonaka et al, 2016; Takagi et al, 2016a; Thevenet et al, 2016; Zhang et al, 2011). Ectopic HMGCS2 has been observed in tissues that lack net ketogenic capacity (Cook et al, 2016; Wentz et al, 2010), and HMGCS2 exhibits prospective ketogenesis-independent ‘moonlighting’ activities, including within the cell nucleus (Chen et al, 2016; Kostiuk et al, 2010; Meertens et al, 1998).…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
“…In physiological conditions, Müller cells release ATP to the extracellular space that is used by microglia to fuel their motility (Wang and Wong, 2014). Accordingly, an effective oxidative and biosynthetic dialogue is established between retinal cell components (Adijanto et al, 2014).…”
Section: Glucosementioning
confidence: 99%
“…Adijanto et al have found that RPE oxidizes lipids to yield and secrete ketone bodies. They propose a cycle in which lipids are taken up by the RPE during outer segment recycling and are oxidized to produce ketones, which are then returned to the photoreceptors and enter the TCA cycle to produce ATP and amino acids (Adijanto et al, 2014). …”
Section: Retinal Cell-specific Metabolismmentioning
confidence: 99%